Penerapan Pajak Pertambahan Nilai (PPN) Terhadap Transaksi E-Commerce Di Indonesia - Alifah Hanif Syakirah; Andi Reski Ananda Putr; Nur Azizah (Indonesian Journal of Taxation and Accounting, 2023)
The aim of this research is to assess Indonesia's capability to increase government revenues through tax revenues from e-commerce transactions. The analytical method used is a metasynthesis of findings in qualitative research on tax compliance. The results of this research show that understanding VAT on transactions also has an important role in the financial education of the younger generation. With a deeper understanding of these obstacles, the government and related parties can design strategic policies and education to increase compliance and ensure the implementation of VAT for e-commerce trade. The government must provide clear information to all people in Indonesia about the purposes and benefits of using VAT in online activities to encourage their participation and compliance. Overall, the success of VAT e-commerce is not only related to tax collection, but also national development, education and financial improvement, not just sustainable food. By fully understanding these barriers, governments and related organizations can create effective policies and training strategies to ensure the fulfillment and success of e-commerce VAT.